A super-large diameter PE pipe and its preparation method and application

By adding modified whisker carbon nanotubes to super-large diameter PE pipes, the problem of insufficient elongation of the pipes after breaking is solved, the toughness and anti-aging properties of the pipes are improved, and it is suitable for marine pipeline engineering.

CN117903512BActive Publication Date: 2025-03-18HAINAN LESSO TECH IND CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311681230.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-08
Publication Date
2025-03-18
Estimated Expiration
2043-12-08

AI Technical Summary

Technical Problem

The existing ultra-large diameter PE pipes have insufficient elongation of breakage, resulting in limited use performance and are prone to damage in marine pipeline projects.

Method used

By adding modified whisker carbon nanotubes to PE pipes, the toughness and strength of the pipes are improved, and internal stress and aging are reduced through the heat transfer of the hollow structure and the heat dissipation at the nanoscale.

Benefits of technology

It improves the elongation of the break and tensile yield stress of the pipe, enhances the anti-aging performance, and meets the application requirements of PE pipes in marine pipeline engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004596232950000071
    Figure BDA0004596232950000071
  • Figure BDA0004596232950000072
    Figure BDA0004596232950000072
Patent Text Reader

Abstract

The present invention belongs to the technical field of special materials for PE pipes, and specifically relates to an ultra-large-caliber PE pipe material and its preparation method and application. The present invention first provides a modified whisker carbon nanotube masterbatch, wherein the whisker carbon nanotube is grafted with a phase change microsphere having a phenolic resin as a shell and n-hexadecane as a phase change core material, and the masterbatch is mixed with PE resin and kneaded to form a masterbatch, and then further made into an ultra-large-caliber PE pipe material with PE resin and carbon black masterbatch. The obtained ultra-large-caliber PE pipe material has good tensile fracture rate and anti-aging performance, and other properties also meet the relevant standard requirements of PE pipes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of special materials for PE pipes, and more specifically, relates to an ultra-large-caliber PE pipe material and a preparation method and application thereof. Background Art

[0002] Super-large diameter polyethylene plastic pipes have the characteristics of light weight, smooth inner wall, good corrosion resistance, convenient construction, and long service life, and have been fully utilized in water supply and drainage engineering applications. Especially in recent years, super-large diameter polyethylene plastic pipes have been widely used in marine pipeline projects such as deep-sea discharge, ocean water intake, and cross-sea water delivery. However, the wall thickness of super-large diameter HDPE pipes is relatively thick, and the production process is difficult to control. Especially when the wall thickness exceeds 30mm, the difference in cooling rate between the inner and outer layers during the cooling process of the pipe causes a large internal stress to be generated after the pipe is finalized, which reduces the elongation at break of the large diameter pipe, resulting in a decrease in the bearing capacity of the PE pipe, reducing the performance of the pipe, and causing the pipe to be easily damaged during the construction process of sinking pipes in the deep sea, positioning pipelines, and trench excavation.

[0003] In order to meet the application of PE pipes in marine water supply projects, the national patent CN 101514769A modifies the PE water supply pipe by adding 3 to 5 parts of zinc oxide, calcium carbonate, barium carbonate, chromium carbonate, silicon dioxide, titanium dioxide, montmorillonite or sodium benzoate or at least one of the above nano-inorganic materials. This patent can effectively increase the rigidity and toughness of the pipe, but this patent is for the PE water supply pipe in GB / T13663-2000, and is no longer applicable to the new standard GB / T13663.2-2018 for PE water supply pipes. In particular, the new standard stipulates that the ash content of new PE water supply pipes is ≤0.1%. The above-mentioned PE water supply pipes no longer meet the national standard requirements, so they are no longer suitable for the field of PE water supply pipes for water supply. And by adding the above-mentioned inorganic particles, they often exist as stress concentration points in the matrix, which can easily cause the interface between the matrix and the inorganic particles to debond when an external load is applied, and damage is more likely to occur. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the defects and shortcomings of the existing ultra-large diameter pipes, which are insufficient elongation at break, and thus cause limited performance of the pipes, and provide an ultra-large diameter PE pipe. The ultra-large diameter PE water supply pipe of the present invention improves the toughness and strength of the pipe by adding modified whisker nano carbon tubes, and reduces the aging phenomenon of the pipe.

[0005] The purpose of the invention is to provide a modified whisker carbon nanotube masterbatch.

[0006] The purpose of the invention is to provide a method for preparing an ultra-large-caliber PE pipe.

[0007] Another object of the present invention is to provide an application of a modified whisker carbon nanotube masterbatch in the preparation of ultra-large diameter PE pipes.

[0008] Another object of the present invention is to provide an application of an ultra-large diameter PE pipe in marine pipeline engineering.

[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:

[0010] The invention provides a modified whisker carbon nanotube masterbatch. The modified whisker carbon nanotube masterbatch is mainly prepared from PE100 resin and modified whisker carbon nanotubes in a mass ratio of 100:0.5-2; the modified whisker carbon nanotubes are mainly prepared from the following components calculated in parts by weight: 0.5-2 parts of whisker carbon nanotubes, 0.5-2 parts of whisker carbon nanotubes, 12-17 parts of resol phenolic resin, 20-25 parts of ethyl acetate, 2-6 parts of acetone, 0.5-2 parts of n-hexadecane and 1-5 parts of sodium dodecyl sulfate.

[0011] Preferably, the whisker carbon nanotubes have an inner diameter of 2 to 5 nm, an outer diameter of 20 to 200 nm, and a length of 1 to 15 μm.

[0012] Preferably, the modified whisker carbon nanotube masterbatch is mainly made of PE100 resin and modified whisker carbon nanotubes in a mass ratio of 100:1; the modified whisker carbon nanotubes are mainly made of the following components calculated in parts by weight: 0.5 to 2 parts of whisker carbon nanotubes, 15 parts of ethyl-resin, 22 parts of ethyl acetate, 5 parts of acetone, 1 part of n-hexadecane, and 3 parts of sodium dodecyl sulfate.

[0013] Furthermore, the modified whisker carbon nanotube masterbatch is mainly prepared by the following steps:

[0014] S1. Preparation of modified whisker carbon nanotubes: whisker carbon nanotubes, resol phenolic resin, ethyl acetate, acetone, n-hexadecane and sodium dodecyl sulfate are mixed in water, stirred, reacted at 130-150°C, cooled to room temperature, centrifuged, and dried to obtain modified whisker carbon nanotubes;

[0015] S2. Preparation of modified whisker carbon nanotube masterbatch: The modified whisker carbon nanotubes prepared in S1 are mixed with PE100 resin, kneaded at 160-180° C., and extruded into granules to obtain modified whisker carbon nanotube masterbatch.

[0016] Furthermore, in step S1, the stirring time is 0.5 to 2 hours; and the stirring speed is 1500 to 3000 rpm.

[0017] Preferably, in step S1, the stirring time is 1 hour and the stirring speed is 3000 rpm.

[0018] Preferably, in step S1, the reaction temperature is 150°C.

[0019] Furthermore, in step S1, the reaction time is 6 to 8 hours; preferably, in step S1, the reaction time is 6 hours.

[0020] Furthermore, in step S2, the banburying time is 10 to 20 minutes.

[0021] A super-large-diameter PE water supply pipe comprises the following components calculated by weight: 100 parts of PE resin, 0.2-0.8 parts of modified whisker carbon nanotube masterbatch, and 0.5-2 parts of carbon black masterbatch; wherein the nominal outer diameter of the super-large-diameter PE pipe is 800mm-2500mm.

[0022] The present invention selects whisker nanotubes because they have a very large aspect ratio and a hollow structure. During the processing, the heat transfer effect of the hollow structure gives more heat to the unplasticized area, solving the defects of slow extrusion speed and low shear frequency of ultra-large-diameter PE pipes in actual production, making the PE resin plasticized more uniformly in all parts of the barrel and improving the elongation at break of the pipe. In addition, the whisker carbon nanotubes dissipate heat at the nanoscale, avoiding the heat accumulation formed in the local part of the pipe due to inadequate water cooling, which causes the reduction of anti-aging performance (reduced oxidation induction time).

[0023] The modified whisker carbon nanotubes of the present invention are grafted with phase change microspheres with phenolic resin as the shell and n-hexadecane as the phase change core material. During the processing, the phase change microsphere material absorbs heat to enhance the activity of the PE resin molecular chain, and the whisker carbon nanotubes are more tightly entangled. The whisker carbon nanotubes are embedded in the non-crystalline region of the PE resin, so that the chain entanglement increases and the content of the lacing molecules increases. During the stress process, the whiskers act as "lacing molecules" to reduce the concentration of internal stress and prevent the breakage of the polymer chain, thereby further improving the anti-aging performance, elongation at break and tensile yield stress of the pipe.

[0024] In addition, the present invention also protects the use of the modified whisker carbon nanotube masterbatch in the preparation of ultra-large diameter PE pipes.

[0025] Furthermore, the method for preparing the ultra-large diameter PE pipe of the present invention specifically comprises the following steps: uniformly mixing the modified whisker carbon nanotube masterbatch, carbon black masterbatch and PE resin prepared by the present invention, conveying them to a single screw extruder, extruding them through a mold, and making a pipe of required diameter.

[0026] At the same time, the present invention also claims protection for the application of the super-large diameter PE pipe in marine pipeline engineering; wherein the marine pipeline engineering includes deep-sea discharge, marine water intake, and cross-sea water transmission.

[0027] The present invention has the following beneficial effects:

[0028] The present invention first provides a modified whisker carbon nanotube masterbatch, wherein the whisker carbon nanotube is grafted with a phase change microsphere having a phenolic resin as a shell and n-hexadecane as a phase change core material, and after being mixed and kneaded with a PE resin to form a masterbatch, it is further made into an ultra-large-caliber PE pipe with a PE resin and a carbon black masterbatch. The modified whisker carbon nanotube masterbatch of the present invention has a very large aspect ratio, and can be used in the preparation of ultra-large-caliber PE pipes through the heat transfer effect of the hollow structure, so that the PE resin can be plasticized more uniformly in all parts of the barrel, and the tensile yield stress and elongation at break of the pipe are increased, giving the ultra-large-caliber PE pipe performance that is superior to the prior art, and other performances also meet the relevant standard requirements of PE pipes. At the same time, since the modified whisker carbon nanotubes dissipate heat at the nanoscale, local heat accumulation is avoided, the concentration of internal stress is reduced, and the breakage of the polymer chain is prevented, thereby improving the anti-aging performance of the pipe. Therefore, the present invention has the potential ability to be processed and produced in large quantities in factories, and can be widely promoted and applied in marine pipeline projects. DETAILED DESCRIPTION

[0029] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0030] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0031] Example 1: A super-large diameter PE marine water supply pipe

[0032] An ultra-large diameter PE ocean water supply pipe is composed of the following components calculated by weight: 100 parts of PE resin; 0.2 parts of whisker carbon nanotube masterbatch; and 0.5 parts of carbon black masterbatch.

[0033] Whisker carbon nanotube: inner diameter: 2-5nm, outer diameter: 20-200nm, length: 1-15μm. (WhiskerCNT-H, Jiangxi Kelaiwei Nanocarbon Materials Co., Ltd.)

[0034] PE resin: Hainan Refining 23050, Carbon black masterbatch: Chongqing Aocai C4153L

[0035] S1. Preparation of modified whisker carbon nanotubes:

[0036] 0.5 parts of whisker carbon nanotubes, 15 parts of phenolic resin, 22 parts of ethyl acetate, 5 parts of acetone, 1 part of n-hexadecane, 3 parts of sodium dodecyl sulfate and 20 parts of deionized water were stirred in a reactor at room temperature for 1 hour at a stirring speed of 3000 rpm. The temperature was raised to 150°C for reaction for 6 hours, and the mixture was centrifuged at 5000 rpm after cooling to room temperature, and then dried at 60°C to obtain the modified whisker carbon nanotubes. The modified whisker carbon nanotubes are phase change microspheres grafted with whisker carbon nanotubes with phenolic resin as the shell and n-hexadecane as the phase change core material.

[0037] S2. Preparation of modified whisker carbon nanotube masterbatch:

[0038] The modified whisker carbon nanotubes prepared by S1 and PE100 are kneaded at 180° C. for 10 minutes at a mass ratio of 1:100; after kneading, they are transported to a twin-screw extruder for extrusion granulation to obtain modified whisker carbon nanotube masterbatch.

[0039] S3. Preparation of extra large PE pipe:

[0040] On the super-large diameter PE pipe production line, the modified whisker carbon nanotube masterbatch prepared by S2, the carbon black masterbatch and PE are evenly mixed in a mass ratio of 0.2:0.5:100 and then extruded through an extruder to produce 1600*94.1mm SDR17 PE super-large diameter pipes.

[0041] Example 2: An ultra-large diameter marine water supply pipe

[0042] An ultra-large diameter ocean water supply pipe is composed of the following components calculated by weight: 100 parts of PE resin; 0.8 parts of whisker carbon nanotube masterbatch; and 2 parts of carbon black masterbatch.

[0043] Whisker carbon nanotube: inner diameter: 2-5nm, outer diameter: 20-200nm, length: 1-15μm. (WhiskerCNT-H, Jiangxi Kelaiwei Nanocarbon Materials Co., Ltd.)

[0044] PE resin: Hainan Refining and Chemical 23050, carbon black masterbatch: Chongqing Aocai C4153L.

[0045] S1. Preparation of modified whisker carbon nanotubes:

[0046] 2 parts of whisker carbon nanotubes, 15 parts of resol phenolic resin, 22 parts of ethyl acetate, 5 parts of acetone, 1 part of n-hexadecane, 3 parts of sodium dodecyl sulfate, and 20 parts of deionized water were stirred in a reactor at room temperature for 1 hour at a stirring speed of 3000 rpm. The temperature was raised to 150°C for reaction for 6 hours, and after cooling to room temperature, the mixture was centrifuged at a speed of 5000 rpm, and then dried at 60°C to obtain the modified whisker nanotubes. After modification, the whisker carbon nanotubes were grafted with phase change microspheres with phenolic resin as the shell and n-hexadecane as the phase change core material.

[0047] S2. Preparation of modified whisker carbon nanotube masterbatch:

[0048] The modified whisker carbon nanotubes prepared by S1 and PE100 are kneaded at 160° C. for 20 minutes at a mass ratio of 1:100; after kneading, they are transported to a twin-screw extruder for extrusion granulation to obtain modified whisker carbon nanotube masterbatch.

[0049] S3. Preparation of super large PE pipe:

[0050] On the super-large diameter PE pipe production line, the modified whisker carbon nanotube masterbatch prepared by S2, the carbon black masterbatch and PE are evenly mixed in a mass ratio of 0.8:2:100 and then extruded through an extruder to produce 1600*94.1mm SDR17 PE super-large diameter pipes.

[0051] Example 3: An ultra-large diameter ocean water supply pipe

[0052] An ultra-large diameter PE ocean water supply pipe is composed of the following components calculated by weight: 100 parts of PE resin; 0.5 parts of whisker carbon nanotube masterbatch; and 1 part of carbon black masterbatch.

[0053] Whisker carbon nanotube: inner diameter: 2-5nm, outer diameter: 20-200nm, length: 1-15μm. (WhiskerCNT-H, Jiangxi Kelaiwei Nanocarbon Materials Co., Ltd.)

[0054] PE resin: Hainan Refining and Chemical 23050, carbon black masterbatch: Chongqing Aocai C4153L.

[0055] S1. Preparation of modified whisker carbon nanotubes:

[0056] 1 part of whisker carbon nanotubes, 15 parts of phenolic resin, 22 parts of ethyl acetate, 5 parts of acetone, 1 part of n-hexadecane, 3 parts of sodium dodecyl sulfate and 20 parts of deionized water were stirred in a reactor at room temperature for 1 hour at a stirring speed of 3000 rpm. The temperature was raised to 150°C for reaction for 6 hours, and after cooling to room temperature, the mixture was centrifuged at a speed of 5000 rpm and then dried at 60°C to obtain the modified whisker carbon nanotubes. The modified whisker carbon nanotubes were whisker carbon nanotubes grafted with phase change microspheres with phenolic resin as the shell and n-hexadecane as the phase change core material.

[0057] S2. Preparation of modified whisker carbon nanotube masterbatch:

[0058] The modified whisker carbon nanotubes prepared by S1 and PE100 are kneaded at 170° C. for 15 minutes at a mass ratio of 1:100; after kneading, they are transported to a twin-screw extruder for extrusion granulation to obtain modified whisker carbon nanotube masterbatch.

[0059] S3. Preparation of extra large PE pipe:

[0060] On the super-large diameter PE pipe production line, the modified whisker carbon nanotube masterbatch prepared by S2, the carbon black masterbatch and PE are evenly mixed in a mass ratio of 0.5:1:100 and then extruded through an extruder to produce 1600*94.1mm SDR17 PE super-large diameter pipes.

[0061] Comparative Example 1

[0062] The raw materials and preparation method used are the same as those in Example 1, except that the whisker carbon nanotubes used are not modified, but are directly kneaded at 160-180° C. for 10-20 minutes at a mass ratio of 1:100; after kneading, they are transported to a twin-screw extruder for extrusion granulation to obtain whisker carbon nanotube masterbatch. Then, on a large-diameter PE pipe production line, the whisker carbon nanotube masterbatch, the carbon black masterbatch and PE are mixed uniformly at a mass ratio of 0.2:0.5:100, and then extruded through an extruder to produce a 1600*94.1mmSDR17 PE ultra-large-diameter pipe.

[0063] Comparative Example 2

[0064] The raw materials and preparation method used are the same as those in Example 2, except that no whisker carbon nanotube masterbatch is added, and the carbon black masterbatch and PE are directly mixed in a mass ratio of 2:100 on a large-diameter PE pipe production line and then extruded through an extruder to produce 1600*94.1mmSDR17 PE ultra-large-diameter pipes.

[0065] Comparative Example 3

[0066] The raw materials and preparation method used are the same as those in Example 1, except that the modified whisker carbon nanotubes in S1 are prepared by adding whisker carbon nanotubes to silane coupling agent at a mass ratio of 100:1 and stirring evenly, and grafting the silane coupling agent onto the whisker nanotubes. Then, 1600*94.1mm SDR17 PE ultra-large diameter pipes are prepared according to the method in Example 1.

[0067] Comparative Example 4

[0068] The raw materials and preparation method used are the same as those in Example 1, except that the stirring speed in the preparation stage of the modified whisker nanotubes in S1 is set to 5000 rpm. Then, a 1600*94.1 mm SDR17 PE ultra-large diameter pipe is prepared according to the method in Example 1.

[0069] Performance Test:

[0070] Tensile tensile yield stress, elongation at break: Test method: Sample preparation according to GB / T8804.1-2003, test according to GB / T8804.3-2003. Take samples along the circumference, make 8 specimens respectively, then prepare samples, list the elongation at break data respectively, and take the average value of tensile yield stress.

[0071] Oxidation induction time: Tested according to GB / T19466.6-2009, test temperature 210℃.

[0072] The standard for judging whether the data results are qualified or not: judged in accordance with GB / T13663.2-2018 "Polyethylene (PE) Pipe System for Water Supply Part 2: Pipes".

[0073] Table 1 Performance data of pipes in Examples 1 to 3

[0074]

[0075] Table 2 Performance data of pipes in comparative examples 1 to 4

[0076]

[0077] It can be seen from the test results of Table 1 and Table 2 that under the same processing technology, the toughness and strength of the ultra-large diameter PE pipes prepared in each embodiment of the present invention are improved. Before adding the whisker carbon nanotubes, the elongation at break of Comparative Example 2 often appears in a certain part below the requirement of ≥350% of the national standard 13663.2. Although the strength of the unmodified whisker carbon nanotubes in Comparative Example 1 is improved, the elongation at break is still unqualified. After adding the silane coupling agent to the whisker carbon nanotubes in Comparative Example 3, although the dispersion performance and elongation at break are partially improved, due to the poor plasticization effect, some parts are still unqualified, and the oxidation induction time is not changed much. Comparative Example 4 increases the stirring speed in the preparation process of the modified whisker carbon nanotubes, which will cause the particle size of the phase change material to be too small during synthesis, so that it is not easy to entangle with PE when grafted to the whiskers, thereby affecting the performance of the pipe. The PE ultra-large diameter pipe with modified whisker carbon nanotubes added in the embodiment is not only plasticized evenly, but also plays a role in strengthening and toughening. At the same time, the ultra-large diameter pipe modified by phase change material can better disperse the nano whiskers, realize nanoscale heat dissipation, avoid the local heat accumulation and the consumption of antioxidant components, reduce aging, and thus increase the oxidation induction time.

[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A modified whisker carbon nanotube masterbatch, characterized in that: The modified whisker carbon nanotube masterbatch is made of PE100 resin and modified whisker carbon nanotubes in a mass ratio of 100:0.5-2; the modified whisker carbon nanotubes are made of the following components calculated by weight: 0.5-2 parts of whisker carbon nanotubes, 12-17 parts of resol phenolic resin, 20-25 parts of ethyl acetate, 2-6 parts of acetone, 0.5-2 parts of n-hexadecane, and 1-5 parts of sodium dodecyl sulfate; The method for preparing the modified whisker carbon nanotube masterbatch comprises the following steps: S1. Preparation of modified whisker carbon nanotubes: whisker carbon nanotubes, resol phenolic resin, ethyl acetate, acetone, n-hexadecane and sodium dodecyl sulfate are mixed in water, stirred, reacted at 130-150°C, cooled to room temperature, centrifuged, and dried to obtain modified whisker carbon nanotubes; S2. Preparation of modified whisker carbon nanotube masterbatch: The modified whisker carbon nanotubes prepared in S1 are mixed with PE100 resin, kneaded at 160-180° C., and extruded into granules to obtain modified whisker carbon nanotube masterbatch.

2. The modified whisker carbon nanotube masterbatch according to claim 1, characterized in that: In step S1, the stirring time is 0.5 to 2 hours; the stirring speed is 1500 to 3000 rpm.

3. The modified whisker carbon nanotube masterbatch according to claim 1, characterized in that: In step S1, the reaction time is 6 to 8 hours.

4. The modified whisker carbon nanotube masterbatch according to claim 1, characterized in that: In step S2, the mixing time is 10 to 20 minutes.

5. Use of the modified whisker carbon nanotube masterbatch according to any one of claims 1 to 4 in the preparation of ultra-large diameter PE pipes.

6. An ultra-large diameter PE pipe, characterized in that: The super-large diameter PE pipe is made of the following components in parts by weight: 100 parts of PE resin, 0.2-0.8 parts of the modified whisker carbon nanotube masterbatch according to any one of claims 1 to 4, and 0.5-2 parts of carbon black masterbatch; wherein the nominal outer diameter of the super-large diameter PE pipe is 800mm-2500mm.

7. The method for preparing the super-large diameter PE pipe according to claim 6, characterized in that: The specific steps include: The modified whisker carbon nanotube masterbatch according to any one of claims 1 to 4, the carbon black masterbatch and the PE resin are uniformly mixed, transported to a single-screw extruder, and extruded through a die to form a pipe of a desired diameter.

8. Application of the super-large diameter PE pipe according to claim 6 in marine pipeline engineering.

9. The use according to claim 8, characterized in that: The marine pipeline project includes deep-sea discharge, ocean water intake, and cross-sea water transmission.

Citation Information

Patent Citations

  • Non-digging PE-specialized service tube

    CN101514769A

  • Nano-whisker modified PE (polyethylene) pipe and preparation method thereof

    CN104479193A

  • Whisker carbon nanotube modified polypropylene crude fiber and preparation method thereof

    CN111945242A